Risk Factor Analysis of Hypertension Occurrence Based on Urban-Rural Location in Indonesia (IFLS Data Study 5) - Ningharto, Bara Bangun; Mandagi, Ayik Mirayanti; Pratama, Rochmad Ardiansyah; Hidayati, Iswana Zahraa (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The World Health Organization (WHO) defines hypertension as a "silent killer" disease because the most of hypertension has not signs or symptoms. Nationally, Indonesia in 2016, the prevalence of hypertension is also higher in urban areas by 31.7% than in rural areas by 30.2%, the prevalence of hypertension is increasing with the increasing of ages. This study aims to analyze the factors that influence the incidence of hypertension and to determine the most influential factor at risk in the incidence of hypertension based on differences in the location of urban-rural respondents. The research design used in this study was observational analytics based on secondary data from the Indonesia Life Survey 5. The population study is the Indonesian community while the total sample as a whole amounted to 14,824. Conclusion: factors that influence the incidence of hypertension in urban and rural areas are BMI, age, education, marital status and smoking status.